Asymmetric Intramolecular Amination Catalyzed with CpIr-SPDO via Nitrene Transfer for Synthesis of Spiro-Quaternary Indolinone - Wei, Shi-Qiang; Li, Zi-Hao; Wang, Shuang-Hu; Chen, Hua; Wang, Xiao-Yu; Gu, Yun-Zhou; Zhang, Ye; Wang, Hong; Ding, Tong-Mei; Zhang, Shu-Yu; Tu, Yong-Qiang (Journal of the American Chemical Society, 2024)
An asymmetric intramolecular spiro-amination to high steric hindering α-C–H bond of 1,3-dicarbonyl via nitrene transfer using inactive aryl azides has been carried out by developing a novel Cp*Ir(III)-SPDO (spiro-pyrrolidine oxazoline) catalyst, thereby enabling the first successful construction of structurally rigid spiro-quaternary indolinone cores with moderate to high yields and excellent enantioselectivities. DFT computations support the presence of double bridging H–F bonds between [SbF6]− and both the ligand and substrate, which favors the plane-differentiation of the enol π-bond for nitrenoid attacking. These findings open up numerous opportunities for the development of new asymmetric nitrene transfer systems.